2000
DOI: 10.1177/106689690000800418
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr Virus-Associated Cholangiocarcinoma with Lymphoepithelioma-Like Component

Abstract: We report the case of a 19-year-old woman who presented with a hepatic mass without cirrhosis. Light microscopy revealed a cholangiocarcinoma having both well-differentiated adenocarcinoma and lymphoepithelioma-like undifferentiated carcinoma components. By immunohistochemistry, the tumor showed strong and diffuse expression for cytokeratin AE1, 5D3, and CK22. The tumor cells were positive for p53 protein (more than 75% of the cells) but negative for bcl-2 and LMP1. Abundant Epstein-Barr virus EBER (1/2) oligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Although there is no predilection for either sex (male: female 7:7), cases of Asian race predominated (11 of 14 patients were Asian). Except for a 19-year-old Hispanic girl reported by Ortiz et al [15] , all patients were adults (average 55.1 years; range 19-71). The 13 cases of biliary LEC reported previously were all intrahepatic cholangiocarcinoma, and this is the first case report of extrahepatic biliary lymphoepithelioma-like cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is no predilection for either sex (male: female 7:7), cases of Asian race predominated (11 of 14 patients were Asian). Except for a 19-year-old Hispanic girl reported by Ortiz et al [15] , all patients were adults (average 55.1 years; range 19-71). The 13 cases of biliary LEC reported previously were all intrahepatic cholangiocarcinoma, and this is the first case report of extrahepatic biliary lymphoepithelioma-like cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Since Hsu et al [12] reported a case of intrahepatic lymphoepithelioma-like cholangiocarcinoma in 1996, only 12 additional cases of LEC of the biliary tract have been reported in the English literature [13][14][15][16][17][18][19][20] . In Table 1, we summarize the clinicopathological features of these 13 cases and the present case of biliary LEC.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoepithelioma‐like cholangiocarcinoma (LELCC) is a rare variant of intrahepatic cholangiocarcinoma (IHCC). Only 16 cases have been reported in the literature, and about 62.5% of these cases were associated with EBV …”
Section: Introductionmentioning
confidence: 99%
“…However, p53 nuclear staining is frequently positive in LELC of other organs [32,38,50] and in more than 50% of nasopharyngeal carcinomas in most series [18,19,31,40]. In this anatomical location, it is frequently associated with EBV [18,31,41], with a strong association between p53 overexpression and EBER status [18].…”
Section: Discussionmentioning
confidence: 96%